Deconstructing the Narrative of “Scatter Investment” in Online Gambling: The Perspective of Maqashid Sharia and a Review of Indonesian Digital Investment Law - Safaruddin Safaruddin (Qiyam Islamic Studies Center Foundation, 2026)
The massive growth of online gambling platforms in Indonesia, particularly games like Higgs Domino Island popularly framed as “Scatter Investment” where “Scatter” refers to a special in-game symbol that triggers bonus rounds or free spins and is often associated with large monetary rewards, reflects a dangerous linguistic and legal distortion that normalizes gambling as an investment activity. This article critically examines the phenomenon of “Scatter Investment” through the dual lenses of Maqashid Sharia and Indonesian investment law. Using a normative-juridical and qualitative approach, this research analyzes classical and contemporary fiqh literature, relevant fatwas of the Indonesian Ulema Council, and Indonesian positive law, including Law No. 25 of 2007 on Investment, the Criminal Code (KUHP), the Electronic Information and Transactions Law (UU ITE), and Qanun Aceh No. 6 of 2014 on Jinayat Law. The study finds that online gambling labeled as investment fails to meet the essential characteristics of investment under both positive law and Islamic economics because it lacks productive activity, creates no real economic value, depends on pure chance, and structurally exploits players. From the Maqashid Sharia perspective, “Scatter Investment” severely violates all five fundamental objectives of the law (al-kulliyat al-khamsah): protection of religion, life, intellect, lineage, and wealth, as it undermines religious observance, damages mental health, destroys rational decision-making, disintegrates families, and causes severe financial harm. The article concludes that the term “Scatter Investment” is a misleading narrative that must be deconstructed theologically, legally, and linguistically, and that online gambling should be treated as a criminal and moral offense rather than an economic opportunity. Policy recommendations include strengthening law enforcement, tightening financial and digital regulations, and mainstreaming Maqashid-based literacy in public education.